2008
DOI: 10.1016/j.jnoncrysol.2007.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Study of trap states in zinc oxide (ZnO) thin films for electronic applications

Abstract: The electrical properties of ZnO thin films grown by pulsed laser deposition were studied. Field-effect devices with a mobility reaching 1 cm 2 /V s show non-linearities both in the current-voltage and in the transfer characteristics which are explained as due to the presence of trap states. These traps cause a reversible threshold voltage shift as revealed by low-frequency capacitance-voltage measurements in metal insulator semiconductor (MIS) capacitors. Thermal detrapping experiments in heterojunctions conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The transmission electron microscopy contrast is characteristic of a nonhomogeneous structure, corresponding to large variations in the local density of the amorphous structure. 22 This suggests that during the densification process, the less dense nanoregions are converted into nanopores of 3-5 nm. A close investigation of the HRTEM clearly shows the difference between the film densities of the spincoated and the inkjet-printed film as determined by the image contrast.…”
Section: Resultsmentioning
confidence: 99%
“…The transmission electron microscopy contrast is characteristic of a nonhomogeneous structure, corresponding to large variations in the local density of the amorphous structure. 22 This suggests that during the densification process, the less dense nanoregions are converted into nanopores of 3-5 nm. A close investigation of the HRTEM clearly shows the difference between the film densities of the spincoated and the inkjet-printed film as determined by the image contrast.…”
Section: Resultsmentioning
confidence: 99%
“…30 A moderately high value of ideality factor in the case of large-area n-ZnO/p-Si heterojunction may be accounted for by the fact that the current conduction across the heterojunction cannot be explained only by the diffusion mechanism. et al 32 with ZnO/p-Si heterojunction confirmed the presence of a trap state located also at 0.32 eV. A very large value of ideality factor in the case of nanoscale heterojunction, on the other hand, suggests that the current flow through individual nanoneedles depends on the local barrier height and the total current is also mainly dominated by the tunneling component.…”
Section: A Structural and Optical Characterizationmentioning
confidence: 90%
“…The data was analyzed using several models, viz. the initial rise time method [23,24], the heating rate method [25,26] and the curve fitting method by Cowell and Woods [27,28].…”
Section: Thermally Stimulated Currentmentioning
confidence: 99%